EP665 Juvenile granulosa cell tumors of the ovary: a retrospective study of 36 patients. (1st November 2019) - Blot-Dupin, M; Maulard, A; Genestie, C; Pautier, P; Bentivegna, E; Leary, A; Chargari, C; Morice, P; Gouy, S
Abstract : Introduction/Background: Granulosa cell tumors account for approximatively 3% of ovarian tumors. The juvenile histological type (JGCT) represents 5% of them, and remains relatively unknown. Our aim was to describe clinicopathologic characteristics and to evaluate prognostic factors. Methodology: We retrospectively studied medical records of 40 patients referred to our center for JGCT between November 2010 and 2018. Results: Thirty-six patients had confirmed JGCT. The mean age was 19, 9 years (range 2, 5 months - 47, 4 years). Abdominal pain (53%), vaginal bleeding (31%), palpable mass (28%), were the most common presenting symptoms. The distribution of FIGO stage was: 16 patients at stage Ia, 17 Ic, 1 IIa, 1 IIIb, 1 IIIc. Thirty-two patients (89%) had conservative surgery. Sixteen (44%) received adjuvant chemotherapy (Ic=13, IIa=1, IIIb=1, IIIc=1), mostly bleomycine/etoposide/cisplatine regimen. The mean follow up was 35 months (range 1 to 204 months). Nine patients recurred (Ia=1, Ic=6, IIa=1, IIIc=1) with a mean time of 12, 1 months (range 1–47). Among them, 4 had a cystectomy at the initial surgery: 3 without adjuvant chemotherapy, 2 died of disease; 4 stage Ic did not received adjuvant chemotherapy neither. Three patients died after a mean of 21, 2 months (range 9, 5–32, 4). At 36 months: progression free survival was 70, 4% [54, 9–90, 2], overall survival was 85, 6% [71, 4–100]. The main prognosis factor of recurrence was advanced FIGO stage (p< 0, 001) . Age >15 years (p= 0, 09) and cytonuclear atypia (p= 0, 08) tended to be associated to relapse too. Intra operative tumor rupture (p= 0, 03) was a significant risk factor of death.We observed 5 pregnancies with term deliveries. Conclusion: The main prognostic factors are: FIGO stage and intra operative tumor rupture. Fertility sparing surgery is safe for stage Ia, reasonable for stage Ic combined with adjuvant chemotherapy. Patients with cystectomy had poor outcome; unilateral salpingo-oophorectomy must be done sytematically. Disclosure: Nothing to disclose.